Global Trends of Green Pesticide Research from 1994 to 2019: A Bibliometric Analysis. (20th March 2021) - Smith, Hein Hendrik; Idris, Oladayo Amed; Maboeta, Mark Steve
Abstract : The fast-growing world population places food production under enormous pressure to ensure food security. One of the most common methods to increase food production is the use of pesticides, but the continuous use thereof has numerous detrimental effects on the environment. The interest in biopesticides for a possible substitute has grown over the past two decades. To determine the research evolution of biopesticides (green pesticides), a bibliometric analysis from 1994 to 2019 was carried out. A total of 580 documents were found eligible in the Scopus database for this analysis. Parameters such as the number of articles, article citations, keywords, source impact, and countries of publication were used to analyse the documents and rank countries based on authors, productivity, article citations, and co-authorship. The analysis reveals production increased significantly from 2009 and has the most published documents in 2019 with a total of 74 articles. Asia's most populous countries, India and China, were ranked first and second, respectively, and the USA third in terms of the most productive countries in the field of plant biopesticides. Countries in Europe and Africa however have fewer publications than expected in this field, given the fact that they are high consumers of pesticides. India, China, and the USA have 4.08%, 2.94%, and 12.5% multiple country publications (MCPs), respectively, with the USA having a stronger collaboration. Finally, there is a clear indication in this study that India and China are taking the lead in substituting synthetic pesticides with the alternative natural plant biopesticide.